Hello, can someone please help me find the formula for the sequence? I know the difference is (-2/3), but I can't seem to figure out the formula. Thanks,
Follow Math Help Forum on Facebook and Google+
The ratio is (-2/3) the nth term is given by $\displaystyle (-8)* \cdot (-2/3)^{n-1}$
Originally Posted by l flipboi l Hello, can someone please help me find the formula for the sequence? I know the difference is (-2/3), but I can't seem to figure out the formula. Try $\displaystyle a_n=\frac{(-2)^{n+3}}{3^{n}},~n=0,1,\cdots$
Hi, The nth term is given by Tn=a+(n-1)d =-8+(n-1)(-2/3) =-11/3(2+n).
Originally Posted by Plato Try $\displaystyle a_n=\frac{(-2)^{n+3}}{3^{n}},~n=0,1,\cdots$ thx, but n is suppose to start at 1. so the first term a1 = -8.
thanks!
Originally Posted by l flipboi l thx, but n is suppose to start at 1. so the first term a1 = -8. That's an easy fix... (!) Replace "n" with "n - 1" in P's solution.
Originally Posted by deepashree Hi, The nth term is given by Tn=a+(n-1)d =-8+(n-1)(-2/3) =-11/3(2+n). fyi, the sequence is geometric, not arithmetic.
Thanks, everyone!
View Tag Cloud